2008
DOI: 10.1103/physrevc.77.034608
|View full text |Cite
|
Sign up to set email alerts
|

Role of bulk energy in nuclear multifragmentation

Abstract: Because of thermal expansion and residual interactions, hot nuclear fragments produced in multifragmentation reactions may have lower nucleon density than the equilibrium density of cold nuclei. In terms of liquid-drop model this effect can be taken into account by reducing the bulk energy of fragments. We study the influence of this change on fragment yields and isotope distributions within the framework of the statistical multifragmentation model. Similarities and differences with previously discussed modifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 49 publications
(84 reference statements)
3
26
0
Order By: Relevance
“…Otherwise the isoscaling phenomenon would not have been observed. Another possible reason for the extracted small value of C sym is that hot fragments themselves at the so-called 'freeze-out' are dilute due to the strong and Coulomb interactions with surrounding nuclei [388]. This picture, however, seems to contradict the basic Fisher hypothesis that the only correlations inside a dilute medium are those due to clusterization.…”
Section: Evolution Of the Symmetry Energy Observed In The Isoscaling mentioning
confidence: 99%
“…Otherwise the isoscaling phenomenon would not have been observed. Another possible reason for the extracted small value of C sym is that hot fragments themselves at the so-called 'freeze-out' are dilute due to the strong and Coulomb interactions with surrounding nuclei [388]. This picture, however, seems to contradict the basic Fisher hypothesis that the only correlations inside a dilute medium are those due to clusterization.…”
Section: Evolution Of the Symmetry Energy Observed In The Isoscaling mentioning
confidence: 99%
“…To properly treat the nuclear composition, multi-nuclei EOS based on nuclear statistical equilibrium (NSE) have recently been developed by some research groups [4,5,6,7]. NSE calculations require not only the ground-state nuclear mass but also the internal partition function of each nuclide.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [4], these two ingredients are incorporated in the form of the free energy of a hot nucleus, with shell corrections being ignored. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of nuclear multifragmentation data showed that, for the results calculated in thermodynamic models to conform to the experimentally observed ones, the established nuclear parameters taken as inputs in these calculations needed subtle changes [21,22,25,26]. Such a fact points out that the properties of the fragments produced in nuclear disassembly might have been modified because of the interaction of the fragments with the embedding environment in which they are created.…”
Section: Discussionmentioning
confidence: 85%
“…The reduction in symmetry energy can have a fair explanation from the thermal and expansion effects of the disassembling system [24]. The surface properties of the hot fragments [25] as well as their bulk energy [26] are also speculated to be modified due to the embedding environment. A quantum statistical approach to the nuclear equation of state taking into account the formation of clusters [27,28] shows that the properties of these clusters are modified due to the medium in which they are formed.…”
Section: Introductionmentioning
confidence: 99%